Biological effects of p38 MAPK inhibitor losmapimod does not translate to clinical benefits in COPD. (September 2017) - Pascoe, Steven; Costa, Maria; Marks-Konczalik, Joanna; McKie, Elizabeth; Yang, Shuying; Scherbovsky, Pablo Saez
Abstract: Rationale: p38 mitogen-activated protein kinase (MAPK) expression is increased in chronic inflammatory disease. Losmapimod, a p38 MAPK inhibitor, has been developed as a potential anti-inflammatory therapy in COPD. Objectives: To evaluate the effect of losmapimod in reducing exacerbations in subjects with moderate-to-severe COPD. Methods: In this double-blind, parallel-group study, subjects at risk of COPD exacerbations and ≤2% blood eosinophils at screening, were randomized 1:1 to losmapimod 15 mg or placebo (variable treatment duration: 26–52 weeks). The primary endpoint was the annualized rate of moderate/severe exacerbations. Using a Bayesian framework, treatment success was defined as >90% posterior probability that the true ratio of the losmapimod/placebo exacerbation rate was <1. Lung function and health status (St George's Respiratory Questionnaire (SGRQ)) were also assessed. Results: A planned interim analysis resulted in early study termination due to the low probability of a successful study outcome; a total of 94 subjects were randomized to placebo and 90 to losmapimod 15 mg, and 14 and 10 subjects respectively completed the study. Losmapimod treatment was not associated with an improvement in the adjusted posterior median annualized exacerbation rate (losmapimod/placebo ratio: 1.04 (95% Cr I: 0.63, 1.73)). The posterior probability for the losmapimod/placebo annualized rate ratio being <1 was 0.44 (success criterion: >0.90). A statistically significant improvement in post-bronchodilator forced expiratory volume in 1 s was seen at Week 26, at the 5% significance level, with losmapimod treatment versus placebo (p = 0.007). Changes from baseline in SGRQ total score were similar in both groups. No new risks or safety signals were identified with losmapimod treatment. Conclusions: Losmapimod treatment did not reduce the rate of exacerbations in, subjects with COPD at high risk of exacerbation and ≤2% blood eosinophils. These data do not support its use as a therapy in COPD in addition to standard of care. Highlights: Losmapimod, a p38 MAPK inhibitor, was developed as an anti-inflammatory COPD treatment. Treatment response in subjects with blood eosinophils ≤2% and frequent exacerbations was tested. Losmapimod was not effective in reducing the moderate/severe COPD exacerbation rate in this population.